Aquatic fungi from Buldhana district - L.C.Nemade1; B. D. Borse3, V. R. Patil1, S. Y. Patil2 (Current Botany, 2011)
<span style="font-size: 8pt; font-family: Byington; mso-fareast-font-family: ’Times New Roman’; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Present paper deals with five species of freshwater hyphomycetes belonging to five genera were isolated from foam samples collected from the river Purna of Buldhana District. Two species viz. Dendrosporomyces prolifer Nawawi, Webster and Davey and Varicosporium scoparium Roldan and Honrubia are being reported for the first time from India. One species viz. Wiesneromyces laurinus (Tassi) Kirk is being reported for the first time form Maharashtra state. Two species viz. Isthmotricladia laeensis Matsushima and Speropsis pedatospora Tubaki are being reported for the first time from Buldhana District. Brief notes and illustration are given for each taxon. Geographical distribution of each species in India is also provided.